Effect of modified housing on growth and physiological performance of crossbred dairy calves during the summer - MAURYA, VIPIN; BHARTI, P K; SINGH, MUKESH; GAUR, G K; SINGH, GYANENDRA; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
The present study was conducted on crossbred (Vrindavani) cattle calves to evaluate the effect of modified housing using different roofing materials on growth and physiological performance of calves during the summer. Calves (24; 6–8 months old) were randomly selected and allocated in 4 groups, viz. control (C): corrugated cemented sheet (CCS) as roofing material, T1: the CCS roof was painted black inside and white outside, T2: polycarbonate plastic sheet as roof; and T3: polycarbonate roof with adjustable height. Overall the average temperature of shed was significantly lower in T1 (24.89±0.08) followed by T3 (27.30±0.10), T2 (28.28±0.04) and C (29.46±0.16). Overall average relative humidity (%) was significantly lower in T3 (62.38±0.30) as compared to T1 (64.54±0.14), T2 (65.68±0.23) and C (66.30±0.30). Overall average temperature humidity index was significantly lower in T1 (76.32±0.30) followed by T3 (76.50±0.16), T2 (77.91±0.05) and C (78.74±0.25). Total body wt gain (kg) was significantly higher in T3 (35.67), followed by T1 (34.83), T2 (34.1) and C (28.16). Overall rectal temperature (°C) and respiration rate (per minute) in afternoon was significantly higher in control as compared to all other treatment groups. It may be inferred that the micro-environment was more conducive in T1 and T3 than control; hence the reflective paints on roof and adjusted higher height of polycarbonate roof may be the desirable choice for animal housing in view of mitigating heat stress during the summer.